2018
DOI: 10.1007/s00415-018-9153-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and outcome associations in AMPA receptor encephalitis

Abstract: Antibody-mediated encephalitis defines a class of diseases wherein antibodies directed at cellsurface receptors are associated with behavioral and cognitive disturbances. One such recently described encephalitis is due to antibodies directed at alpha-amino-3-hydroxy-5methyl-4isoxazolepropionic acid receptors (AMPAR). This entity is exceptionally rare and its clinical phenotype incompletely described. We present findings from two cases of AMPAR encephalitis that exemplify variability in the disease spectrum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 54 publications
2
62
0
Order By: Relevance
“…In a case series, the sparing of the primary motor cortex occurred in half of the abnormal FDG‐PET scans of limbic encephalitis (Masangkay, Basu, Moghbel, Kwee, & Alavi, ). Bilateral motor cortex sparing was also observed in the FDG‐PET of a case of anti‐AMPAR encephalitis (Laurido‐Soto et al, ). In our patients, cortical hypometabolism also did not include primary motor cortex.…”
Section: Discussionmentioning
confidence: 82%
“…In a case series, the sparing of the primary motor cortex occurred in half of the abnormal FDG‐PET scans of limbic encephalitis (Masangkay, Basu, Moghbel, Kwee, & Alavi, ). Bilateral motor cortex sparing was also observed in the FDG‐PET of a case of anti‐AMPAR encephalitis (Laurido‐Soto et al, ). In our patients, cortical hypometabolism also did not include primary motor cortex.…”
Section: Discussionmentioning
confidence: 82%
“…The fourth case was a 44‐year‐old man with thymoma who was treated with thymectomy, methylprednisolone, IVIg, and rituximab. Finally, he successfully returned to work as a business manager (Laurido‐Soto et al, ). In contrast to the other four cases, our patient was a 26‐year‐old male who was diagnosed with suspected lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…His results showed that the mortality rate of anti‐AMPAR encephalitis was 16% (9/55). While tumor was identified in 67% cases (Laurido‐Soto et al, ). Unfortunately, there are no similar studies on anti‐CRMP5 encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies bind to the α1 subunit of glutamate receptors. Anti-glutamate receptor antibody-positive encephalitis patients have been considered variants associated with progressive encephalomyelitis, stiffness, myoc- [20,23,28,36] LGI1 [7,11] Caspr2 [7,16] AMPAR [37,39,48] GABAR [40][41][42][43] Glutamate R [45,46,49 lonus, and other symptoms of stiff-person syndrome. However, these diseases are characterized by stiff stimulus-sensitive spasms, myoclonus, autonomic dysfunction, and brainstem lesions [45].…”
Section: Anti-glutamate Receptor Encephalitismentioning
confidence: 99%